Insights into the trace Sr2+ impact on the gel properties and spatial structure of mutton myofibrillar proteins. (February 2023) - Zhao, Bing; Zhang, Yuyu; Sun, Baoguo; Wang, Shouwei; Zang, Mingwu; Wang, Hui; Wu, Qianrong
Graphical abstract: Highlights: Trace Sr 2+ interacted with MPs and changed the secondary structure of MPs through intermolecular interactions. Sr 2+ promoted the cross-linking of MPs and facilitated the formation of stable gel structures. Sr 2+ could promote the formation of ionic bonds and disulfide bonds. Sr 2+ had a strong interaction with hydrophilic amino acids and acidic amino acid in MPs of sheep myosin. Abstract: Myofibrillar proteins (MPs) and the quality of meat strongly depend on the properties of MP gels, which in turn depend on several parameters that include the thermal history and the concentration of metal ions. Strontium element (Sr) widely exists in mineral water and is found as strontium ions (Sr 2+ ), which is an essential trace element for humans. This study investigated the effects of trace Sr 2+ on the structure–function relationship of mutton MPs, as well as their gels with water. Trace concentrations of Sr 2+ were found to significantly alter the conformation of the MPs. An increase in Sr 2+ concentration was associated with a reduction in the tightness and strength of the gel and a significant increase in its water-holding capacity As compared to the untreated control sample, the solubility, particle size, and the magnitude of the Zeta potential of the gels increased by 13.03 %, 12.62 %, and 19.73 %, respectively, whereas the water retention capacity and the gel strength increased by 23.13 % and 21.90 %, at a Sr 2+ concentration of 5.0 mg/L. Molecular docking predicted an increase in ionic bonds and disulfide bonds because Sr 2+ had a strong interaction with hydrophilic amino acids and acidic amino acids. The analysis of molecular forces further verified the significant facilitation of interactions between MP molecules with the induction of Sr 2+ . As compare to the untreated control group, the ionic and disulfide bonds increased by 141.17 % and 66.94 %, when treated with 5.0 mg/L Sr 2+ . These changes were likely due to the enhancement of protein–protein interactions caused by Sr 2+, which could induce MP molecules to properly unfold and aggregate in gel formation. The results could provide a basis for improving the texture and the quality of meat and meat products.